Institutional environment as a precondition for improving the technological progress of construction - Zeltser, R. (Ways to Improve Construction Efficiency, 2020)
The legislation of Ukraine on the regulation of urban planning activities establishes the legal and organizational foundations of urban planning activities, which are aimed at ensuring sustainable development of territories, taking into account State, public and private interests. In accordance with the legislative acts, a number of government decrees, orders of the Ministry of Development of Communities and Territories of Ukraine (formerly - the Ministry of Regional Development of Ukraine), state building codes (new or amended from among the current ones) have been developed. There is an urgent need to analyze the situation and further improve the legal regulation of construction, including permitting and approval procedures for the organization and management of construction in accordance with legislation and regulations, adaptation of regulatory policy to European standards as a prerequisite for improving organizational and technological processes of construction and determining their effectiveness. Based on this goal, the following set of issues is consistently considered: contractual relations in capital construction; main participants in the construction - the customer and contractor, investor, developer, etc .; conditions for concluding a contract; terms of performance of works (construction of object); calendar schedule of works; contract price and estimated cost of construction; types of contracts and their characteristics; the rights of the customer and the contractor; contracts for design and research work; methods of economic evaluation of options for the organization of technological processes of construction. Currently, work is underway to improve the legislation on the organization of construction activities, namely: architectural and construction control and supervision, permitting procedures in construction, licensing, self-regulation in urban planning, electronic systems and BIM-technology, technical regulation in construction and more. In this regard, the current guidelines will be clarified with the release of new laws and regulations.